Study of dorsal wall of sacrum - Nagendrappa, Rashmi Benaganahalli; KS, Jayanthi (International Journal of Research in Medical Sciences, 2017)
Background: Sacrum is a large triangular bone formed by fusion of five sacral vertebrae. The opening present at the caudal end of sacral canal is known as sacral hiatus and is formed due to the failure of fusion of lamina of fifth sacral vertebra. Objective of current study was to study the anatomical variations of dorsal wall of sacrum in order to clarify the structural variations of sacral hiatus and surrounding structures for improving the reliability of caudal epidural block Methods: The present study was done on 50 male and 50 female dry human sacra after calculating the sacral indices and sexing of sacra. The dorsal wall of sacrum was studied with respect to composition of sacrum, level of sacral hiatus, deficiencies and apertures in the bony dorsal wall and also for the presence and absence of sacral cornua. Results:The level of apex of sacral hiatus can vary from upper part of S2 to lower part of S5. The most common position was at S4 (64%). Elongated sacral hiatus at the level of S2 was present in 4% of cases. Sacrum had normal 5 segments in 70% of cases, 4 segmented sacra were observed in 4% of cases, sacralization of 5th lumbar vertebra in 7%, coccygeal ankylosis in 19% of cases. Less extensive apertures in the bony dorsal wall of sacral canal were observed in 29% of sacra. Conclusion:The dorsal wall of sacrum has anatomical variations. Understanding these variations may improve the reliability and success of caudal epidural anesthesia.